Students' expectation towards library' services - Alhaderi, Sami; Ishak, Khairol Anuar; Ahmed Fawzi, Dzulhilmi (2017)
The Purpose: The main purpose of this study is to identify the factors that effecting the satisfaction of students and visitors toward the university library.This paper reports a part of a quantitative study that aims to improve the quality of researches among master and PhD students throughout evaluating the library’s performance by measuring the users’ satisfaction with (a) library’s service quality, library resources and (b) library facilities provided by academic library in university Utara Malaysia.The methodology is that data were collected through a survey of 360 respondents using convenience sampling technique.A nonparametric test using the one-way analysis of variance (ANOVA) was used to analysis satisfaction scores of the respondents. The results of the study revealed that on the average, the respondents were quite satisfied with the library services if these services met their expectation.Also, library facilities have direct effect on the student’s satisfaction and that student dissatisfy from library resources.The mean significant of the study is to conduct user satisfaction surveys as a means of identifying areas for service improvement and ensuring that it remains responsive to help in justifying resources and improving the services. Hence, there is a need for university libraries to understand the user needs and satisfy their information and research needs.In order to support in an ongoing learning activities. The study provides literature on user satisfaction of library services.